The politics of romanticism: the social contract and literature - Beenstock, Zoe (University Press, 2017)
The Politics of Romanticism examines the relationship between two major traditions which have not been considered in conjunction: British Romanticism and social contract philosophy. She argues that an emerging political vocabulary was translated into a literary vocabulary in social contract theory, which shaped the literature of Romantic Britain, as well as German Idealism, the philosophical tradition through which Romanticism is more usually understood. Beenstock locates the Romantic movement's coherence in contract theory's definitive dilemma: the critical disruption of the individual and the social collective. By looking at the intersection of the social contract, Scottish Enlightenment philosophy, and canonical works of Romanticism and its political culture, her book provides an alternative to the model of retreat which has dominated accounts of Romanticism of the last century.